Vogue : the covers - Kazanjian, Dodie (New York : Abrams, 2011)
"An illustrated history of the iconic fashion magazine's cover, this book chronicles over 100 years of the images that have influenced past and present style"--
1890s to 1900s : the mauve decades -- '10s : shocks and murmurs -- '20s : the twenties roar -- '30s : night and day -- '40s : I'll be seeing you -- '50s : High society -- '60s : all you need is love -- '70s : all the president's men -- '80s : booms and busts -- '90s : pulp fictions -- 2000s : survivors.
Includes index.
boek
Keywords: Vogue -- Illustrations